Внутрішньовідомчий контроль за діяльністю органів Національної поліції як складова мінімізації корупційного ризику - Шатрава, С. О.; Shatrava, S. O.; ORCID: http://orcid.org/0000-0002-7072-961X (Юридичний науковий електронний журнал. – 2018. – № 1. – С. 146-149, 2018)
В статті доведено, що внутрішній контроль є складовою частиною системи забезпечення внутрішньої безпеки системи МВС України, яка покликана протидіяти як внутрішнім, так і зовнішнім загрозам. Наголошено, що внутрішні загрози зумовлені протиправними та корупційними діями працівників правоохоронного органу, зловживанням наданими їм повноваженнями. Виокремлено основні напрямки, спрямовані на покращення діяльності Національної поліції із забезпечення внутрішнього контролю.

The article shows that internal control is an integral part of the internal security system of the Ministry of Internal Affairs of Ukraine, which is designed to counteract both internal and external threats. It is emphasized that under the internal control of the activities of the National Police, one should understand the system of measures aimed at: firstly, ensuring compliance with the police principle of the rule of law and the protection of human rights and fundamental freedoms, as well as the requirements of legislation and departmental legal acts; and secondly, the prevention, prevention and suppression of police offenses; thirdly, effective, comprehensive, objective and fair internal investigations of offenses committed by the police, as well as cases of the use of physical measures, special means and firearms that caused the infliction of bodily harm or death of a person; fourthly, the protection of policemen from unlawful encroachment and threats; fifth, counteracting attempts to penetrate the criminal police system of the National Police. It is proved that one of the effective tools for preventing corruption is the conduct of official investigations into the activities of the National Police in each case of bringing the police to account for corruption offenses and offenses related to corruption. The main directions aimed at improving the activities of the National Police to ensure internal control are identified.

В статье доказано, что внутренний контроль является составной частью системы обеспечения внутренней безопасности системы МВД Украины, которая призвана противодействовать как внутренним, так и внешним угрозам. Отмечено, что внутренние угрозы обусловлены противоправными и коррупционными действиями работников правоохранительного органа, злоупотреблением предоставленными им полномочиями. Выделены основные направления, направленные на улучшение деятельности Национальной полиции по обеспечению внутреннего контроля.
Шатрава С.О. Внутрішньовідомчий контроль за діяльністю органів Національної поліції як складова мінімізації корупційного ризику [Електронний ресурс] / Шатрава С.О. // Юридичний науковий електронний журнал. – 2018. – №1. – С. 146-149 . – Режим доступу: http://lsej.org.ua/1_2018/42.pdf.
Keywords: внутрішньовідомчий контроль; корупційний ризик; корупційні правопорушення; службове розслідування; corruption risk; internal control; corruption offenses; official investigation; внутрішньовідомчий контроль; корупційний ризик; корупційні правопорушення; службове розслідування; Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; поліція; полиция; police; корупція; коррупция; corruption; коррупционный риск